2012
DOI: 10.1103/physrevb.85.205420
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface modification on the quality factor of microresonators

Abstract: Influence of surface modification on the quality factor of microresonators Ergincan, O.; Palasantzas, G.; Kooi, B. J. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Noise measurements were performed to determine the quality factor (Q) as a function of gas pressure P for microresonators in cantilever form with systematically modified surfaces. In the free-molecular regime, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
0
20
1
1
Order By: Relevance
“…In general, the vibrational frequencies of NEMS are dependent on surface effects [181][182][183]. For example, the surface modification may result in an undesirable decrease in the Q-factor [181] that is directly related to the detection limit [182,184] as shown in Eq. (14).…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…In general, the vibrational frequencies of NEMS are dependent on surface effects [181][182][183]. For example, the surface modification may result in an undesirable decrease in the Q-factor [181] that is directly related to the detection limit [182,184] as shown in Eq. (14).…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…[15]. Ergincan et al [16] have performed a systematic study on the dependence of Q-factor on the surface of commercial MCs at various gas pressures, covering the entire range from the free molecular up to continuous regime (ambient pressures ∼1 atm). They have shown that, in the molecular regime Q scales with pressure P as 1/P, while in continuous regime the scaling changes to ∼1/ √ P. In the present work, we have studied the desorption kinetics of water molecules on an uncoated Si MC with a native grown SiO 2 layer, in dynamic mode.…”
Section: Introductionmentioning
confidence: 99%
“…19 but for cantilevers with systematically modified surfaces. 20 At higher pressures, within the molecular regime, Q showed the typical inverse linear dependence on pressure Q $ P À1 . 19 However, in the molecular regime the Q factor also showed a strong dependence on surface morphology as indicated by surface areas calculations using measured roughness data obtained by atomic force microscopy (AFM), and compared to those obtained from Q $ P À1 plots.…”
mentioning
confidence: 98%
“…19 However, in the molecular regime the Q factor also showed a strong dependence on surface morphology as indicated by surface areas calculations using measured roughness data obtained by atomic force microscopy (AFM), and compared to those obtained from Q $ P À1 plots. 20 However, so far a detailed systematic experimental study of the influence of surface area on the Q factor of resonators within the continuum regime, where dissipation is the highest, is still missing. Hence, this will be the topic of the present paper, where we explore the dependence of the Q factor on the surface area of commercial microcantilevers ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation